Ticks (Acari: Ixodidae) identification in dual purpose cattle production systems from Chone Canton, Manabí Province, Ecuador - Lugo-Almarza, María (2023)
Ectoparasites, among which are ixodids, cause direct damage to animal’s health due to traumatic and hematophagous actions, and indirect for transmission of pathogenic agents. The control depends on biology and epidemiological importance of each particular species, therefore, to be efficient its identification is necessary. To identifying the species of ixodids in dual purpose cattle production systems the Chone Canton of Province of Manabi, Ecuador, an investigation was carried out in 16 production units, where 1,440 specimens of a total of 288 animals were captured, whose species were identified through of morphological keys. Identified specimens belong to two species, Rhipicephalus Boophilus microplus and Amblyomma cajennense, 88.75% and 11.25%, respectively. Rhipicephalus B. microplus showed high prevalence, while A. cajennense was low, in the Chone Canton of Manabi Province.